A Study of digital literacy among the marginalizes in Thailand: Issues, challenges for implementation and the way forward - Intraratat, Kamolrat; Lomchavakarn, Piyachat; Boonsiri, Karn; Ng, Khar Thoe; Intaratat, Duangkamol (Edelweiss Applied Science and Technology, 2024)
The concerns about digital literacy in Thailand especially relevant to fake news, disinformation, and misinformation keep increasing and creating a multifaceted challenges to various sectors of Thai society i.e. financial, commercial, politics, society, and health-related. Among the areas identified include digital contents creation, dissemination, and social media enabling various information with complex challenges such as the proliferation of fake news, disinformation, and misinformation affected more kinds of negative effects currently. This study employs mixed-research method quantitative (survey questionnaire) and qualitative (Focus group discussion, observation, interview) data collection and analysis. A total of 315 samples and key informants were involved as well as grouped under 5 categories: marginal youths, elderly, community leaders, teachers, also government workers focusing on digital literacy knowledge and skills relevant to fake news. It also highlights the relevant contexts i.e. regulatory frameworks and mechanisms driven by key agencies in Thailand. Two main results were revealed that reflected the objectives of the study accordingly: The first objective is (1) overview of digital literacy and how to achieve it. The findings summarized from survey questionnaire include 1.1) even regulations exist found inadequate enforcement and low public awareness call for more effective and collaborative communication from all partners starting from the government agencies; 1.2) urgent need for public awareness communication campaigns emphasizing all the marginalized groups. Youths expressed in the interviews about their contribution to help reduce all kinds of fake news; 1.3) support more friendly ICT context provision such as availability, affordability, accessibility, usability, and useful information. The second objective is (2) mechanism for digital skills empowerment. The feedback from key informants include: 2.1) strengthening digital literacy skills among all marginalized groups to be a smart citizen then can help protecting themselves, their families and their communities; 2.2) all agencies from policy to local i.e. community leaders, educational institutions, private sectors, social media companies, civil society, and others must synergized more contributions; 2.3) educational institutions must design digital literacy academy with digital new-skills for the marginalizes, ensuring them for their safety and future job demands; 2.4) private sectors should support and co-designing digital products and services that address all current needs; 2.5) local government, and all partners should take an active collaboration and enforcement. The study concluded with implications and suggestions for future research in line with SDGs.